An achievement test in English for grade four pupils of Paniqui, Tarlac (with four linguistic backgrounds) - Beltran, Ligaya L. ([Quezon City s.n.], 1973)
This is an achievement test intended for grade four learners of English in Paiqui, Tarlac with four linguistic backgrounds, namely: (1) Ilocano, (2)Pampango, (3) Pangasinan, and (4) Tagalog. It attempts to assess the achievement of the grade four pupils in the three elements of the English language: pronunciation, vocabulary, and structure.
Thesis (M. Ed.)--University of the Philippines.
Keywords: English language -- Examinations, questions, etc